Clay Minerals in Nature Their Characterization, Modification and Application - Valaškova, Marta; Simha Martynkova, Gražyna (IntechOpen, 2012)
Clay is an abundant raw material which has a variety of uses and properties depending on their structure and composition. Clay minerals are inexpensive and environmentally friendly naturally occurring nanomaterials, thanks to their 1 nm thick silicate layers, in all types of sediments and sedimentary rocks. The book chapters have been classified according to their characteristics in topics and applications. Therefore, in the first section five chapters is dedicated to the characterization and utilization of clay minerals in deposits. The second section includes four chapters about the significance of clay minerals in soils. Third section is devoted to different aspects of clay minerals research, especially to the characterization of structure and modifications for their application.